Factors Affecting Optimal Postural Reduction in Posterior Percutaneous Screw Fixation for Neurological Intact in Thoracolumbar Burst Fracture - Tanaviriyachai, MD, Terdpong; Choovongkomol, MD, Kongtush; Piyapromdee, MD, Urawit; Sudprasert, MD, Weera; Jongkittanakul, MD, Sarut (Journal of Southeast Asian Orthopaedics, 2022)
Background: Optimal reduction of kyphosis is a goal in the surgical treatment of thoracolumbar burst fracture. Several factors are known to limit the amount of posterior surgical reduction. However, few comprehensive assessments of postural reduction in posterior percutaneous screw fixation have been reported. Objectives: To determine the relevant factors affecting the optimal anterior vertebral restoration in the percutaneous posterior surgical treatment of neurologically intact thoracolumbar burst fracture. Materials and Methods: Seventy-seven consecutive patients who underwent posterior percutaneous screw fixation for thoracolumbar fracture (T11–L3) burst fracture were included. The patients were divided into sufficient reduction group (postoperative anterior vertebral height correction; AVH ratio ≥ 80%) and insufficient reduction group (postoperative anterior vertebral height correction; AVH ratio < 80%). Clinical characteristics including sex, age, body mass index, time to operation, injury level, and intraoperative blood loss, as well as radiologic characteristics including fracture morphology, fracture deformity, canal stenosis, and fixation techniques were investigated to determine the relevant factors. Results: The mean AVH of insufficient reduction group (n = 21) was 72.03±5.46%, and sufficient reduction group (n=56) was 90.45±6.48%. The relevant factors for insufficient reduction, as identified by univariate analysis, were time to operation > 7 days (OR, 12.19; 95% CI, 1.42-104.89), preoperative kyphosis ≥ 20o (OR, 6.25; 95% CI, 1.86-20.96), preoperative anterior vertebral compression ratio ≥ 0.5 (OR, 2.67; 95% CI, 0.02-0.41), and preoperative canal stenosis ≥ 50% (OR, 0.14; 95% CI, 0.03-0.63). However, multivariate analysis demonstrated that time to operation > 7 days (OR, 9.28; 95% CI, 1.46-58.99), burst fracture type A4 (OR, 20.88; 95% CI, 1.08-402.02), comminution 30-60% (OR, 0.02; 95% CI, 0-0.44) and comminution > 60% (OR, 0.008; 95% CI, 0-0.37) were significant risk factors for insufficient postural reduction. Conclusions: Insufficient postural reduction in posterior percutaneous screw fixation after thoracolumbar burst fracture affected by delayed operation time > 7 days, burst type A4 fracture and comminution more than 30%.